The Air Quality and Detection of Streptococcus pneumoniae in the Pediatric Ward of Dr. Hasan Sadikin Hospital Bandung - Thiban Raj Manoraj; Yanti Mulyana; Sri Endah Rahayuningsih (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Nosocomial infection can be acquired by inhalation of droplets from contaminated air. In children, nosocomial pneumonia is mainly caused by Streptococcus pneumoniae. This study aimed to explore the air quality level and to detect Streptococcus pneumonia in the air of the Pediatric Ward of Dr. Hasan Sadikin Hospital, Bandung. Methods: This was an observational descriptive study conducted in the Pediatric Ward of Dr. Hasan Sadikin Hospital in November 2012. The different number of modified tryptic soy agar (TSA) plates with 4% blood were exposed and placed in various rooms of the ward for 30 minutes between 12.00 pm to 1.00 pm at heights between 1.0m to 1.5m and according to the respectively room air volume. After exposure, these plates were then incubated for 48 hours at 35°C. The Colony Forming Units (CFU) on each plate was counted per Replicate Organism Detection and Counting (RODACTM). Detection of Streptococcus pneumonia was performed by detecting any round α-hemolytic colonies on the TSA plate, confirmed by Gram staining, optochin susceptibility test, and the bile solubility test. Result: The air quality in 13 rooms of the Pediatric Ward was generally poor ranging from 27.5 to 232.0 CFU/30 min, however, the concentration of microorganisms per cubic meter air was from 0.198 to 4.296 CFU/m3. Moreover, Streptococcus pneumoniae was not present in the air of the ward.Conclusions: Although Streptococcus pneumoniae has not been detected, the air quality in the Pediatric Ward of Dr. Hasan Sadikin Hospital, Bandung is generally poor. General precautions need to be enhanced to increase the air quality in the hospital.